2022
DOI: 10.3389/fphar.2022.965902
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of ethnomedicine, phytochemistry, and pharmacology of Cyperi Rhizoma

Abstract: Cyperi Rhizoma (CR) is the dry rhizome of Cyperus rotundus L., a Cyperaceae plant. It has a long history of clinical medication and is known as the “holy medicine” of gynecology. CR smells sweet and bitter. It has the effect of soothing the liver and relieving depression, regulating qi, regulating meridian and relieving pain. It can be used to treat liver qi stagnation, chest pain, spleen and stomach qi stagnation, hernia pain, irregular menstruation and other diseases. At present, the main chemical constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 101 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Plant-derived flavonoids have a wide range of anti-inflammatory and antioxidant activities and can effectively block toxic pathways associated with neurodegenerative disease pathology [ 93 ], including kaempferol, quercetin, baicalin and so on.…”
Section: Potential Mechanisms Of Traditional Chinese Medicine Natural...mentioning
confidence: 99%
“…Plant-derived flavonoids have a wide range of anti-inflammatory and antioxidant activities and can effectively block toxic pathways associated with neurodegenerative disease pathology [ 93 ], including kaempferol, quercetin, baicalin and so on.…”
Section: Potential Mechanisms Of Traditional Chinese Medicine Natural...mentioning
confidence: 99%
“…Rhizoma Cyperi is known for its ability to clear the liver, relieve depression, regulate qi, and relieve menstrual pain. Modern studies have shown that the chemical components of Rhizoma Cyperi mainly include terpenes, flavonoids, alkaloids, sugars, sterols, and other components, which have pharmacological effects such as antitumor, antidepression, anti-inflammatory, antibacterial, antioxidation, and hypoglycemic effects [ 58 ]. Volatile oils, including α-vanvanone, vanvanolone, etc., are the main components of Rhizoma Cyperi, with a mass fraction of 0.65–1.4% [ 59 , 60 ].…”
Section: Pharmacological Study Of Seven Herbs In Chsgmentioning
confidence: 99%
“…Cyperi Rhizoma (CR), the dried rhizome of Cyperus rotundus L. of the plant family Cyperaceae, has a long history of clinical use and is referred to as the 'holy medicine' in gynaecology [4]. Pharmacological studies have shown that CR has multiple properties, including antioxidant, anti-in ammatory, antidepressant, antipyretic, analgesic, antitumour, hypoglycaemic and antibacterial effects.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional approach to treating endometriosis is surgical removal of the lesions and hormonal suppression, but these treatments are often associated with side effects and a high rate of recurrence [2]. Against this backdrop, complementary and alternative medicine (CAM) has recently gained popularity due to its low side effects and high e cacy [3].Cyperi Rhizoma (CR), the dried rhizome of Cyperus rotundus L. of the plant family Cyperaceae, has a long history of clinical use and is referred to as the 'holy medicine' in gynaecology [4]. Pharmacological studies have shown that CR has multiple properties, including antioxidant, anti-in ammatory, antidepressant, antipyretic, analgesic, antitumour, hypoglycaemic and antibacterial effects.…”
mentioning
confidence: 99%